PARTICULATE AND SNOW NITRITE IN THE SPRING ARCTIC TROPOSPHERE - Li, S. M. (ATMOSPHERIC ENVIRONMENT PART A-GENERAL TOPICS, 1993)
In the spring of 1986 and 1989, particle nitrite was measured at Barrow, Alaska, by filter sampling and by ion chromatographic analysis. Particle nitrite concentrations averaged 2.9 +/- 3.4 and 2.6 +/- 2.0 ppt (molar ratio) in 1986 and 1989, respectively. Both seasons showed diurnal variations with higher concentrations during the day which might have been caused by daytime down mixing. In 1989, nitrite was determined in several snow samples with concentrations between 0 and 0.18 mu mol l(-1). Particle nitrite was probably in disequilibrium with gas phase, suggesting a heterogeneous source for gaseous HONO. A relationship between particle nitrite and sodium ions suggests that sea salt could be involved in nitrite formation, perhaps through hydrolysis of nitryl halides.